2011
DOI: 10.1073/pnas.1105200108
|View full text |Cite
|
Sign up to set email alerts
|

In situ engineering of the lymph node microenvironment via intranodal injection of adjuvant-releasing polymer particles

Abstract: Recent studies have demonstrated a simple, potentially universal strategy to enhance vaccine potency, via intralymph node (i.LN) injection. To date, intranodal immunization studies have focused on the delivery of unadjuvanted vaccines (e.g., naked DNA, peptide, or protein). We hypothesized that combining i.LN vaccination with controlled release biomaterials permitting sustained dosing of molecular adjuvants to the local tissue microenvironment would further enhance this promising vaccination strategy. To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
220
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 33 publications
0
220
0
Order By: Relevance
“…Compared with current published studies, our TRP-2-based therapeutic nanoparticle vaccine is very potent at the low doses used for antigen and adjuvant (18,39,40). Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Compared with current published studies, our TRP-2-based therapeutic nanoparticle vaccine is very potent at the low doses used for antigen and adjuvant (18,39,40). Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 61%
“…4B) induced by targeting the vaccine to the tdLN led to regression of early-stage tumors and more impressively of tumors having reached the Swiss legal limit of 1 cm 3 . In the literature, cancer vaccines are usually administered when the tumors are 5 to 7 mm in diameter or even before they are detectable, and also do not usually induce this high number of TAA-specific CD8 þ T cells in the blood and the LNs (17,19,30,38,44), thus emphasizing the benefits of nanoparticle-mediated targeting of antigen and adjuvant to DCs in the tdLN (18,38,45). We noted, however, that after regressing some tumors grew back.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This targeting has been shown to enhance cytotoxic T-cell responses when the TLR7 agonist is applied together with antigen in the context of vaccination (Jewell et al, 2011;Nuhn et al, 2016). In addition, lymph node targeting of TLR ligands can reduce systemic levels of proinflammatory cytokines (Bourquin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%